2020
DOI: 10.14198/fem.2020.35.05
|View full text |Cite
|
Sign up to set email alerts
|

Through the lens of single parenthood: a comparative snapshot of the impact of neoliberal welfare, housing and employment policies on single mothers in the UK and Sweden

Abstract: The paper considers why feminists working on gender mainstreaming in the UK looked to Sweden for models to effect structural change and why in recent years the models in Sweden are deficient, embodying an ever-increasing blind spot to the socio/economic constraints experienced by single parents, migrant mothers the most marginalised. Referencing academic feminist research in Sweden and the UK, as well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…När Bristol One Parent Project (BOPP) initierades av en grupp ensamstående mammor i mitten av 1980-talet var stödet för självorganiserade aktivistiska grupper mycket begränsat i Storbritannien (Cohen & Samzelius 2021). I stället vände BOPP blicken mot den Europeiska Gemenskapen, som under denna tid lanserade ett nytt ambitiöst fattigdomsprogram (Room 1984).…”
Section: En Möjliggörande Kontextunclassified
“…När Bristol One Parent Project (BOPP) initierades av en grupp ensamstående mammor i mitten av 1980-talet var stödet för självorganiserade aktivistiska grupper mycket begränsat i Storbritannien (Cohen & Samzelius 2021). I stället vände BOPP blicken mot den Europeiska Gemenskapen, som under denna tid lanserade ett nytt ambitiöst fattigdomsprogram (Room 1984).…”
Section: En Möjliggörande Kontextunclassified
“…Universality could be maintained particularly through funding municipal services, including education, healthcare and welfare. More recently, scholars indicated that even social-democratic welfare systems, such as Sweden, embrace conditionality in its cash transfers (Samzelius and Cohen, 2020). At the same time, in-kind support, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, welfare rights advocates, feminist activists, academics and policy-makers had turned to Sweden for inspiration and it was in particular the access to affordable wrap-around childcare that was envied. However, the large disparity in poverty rates between different household types in Sweden suggested that this question was more complex (see Cohen & Samzelius 2020;Lister 2009).…”
Section: On the Motive Forcementioning
confidence: 99%
“…Contrary to places where a breadwinner model continued to dominate, the central guiding principle of social policy towards single mothers in Sweden has, since the 1970s, been one of integration and inclusion within policies for gender equality and labour-market participation (Hobson & Takahashi 1997). In contrast, during this time, in the UK a large proportion of single mothers lived in poverty and faced discrimination when trying to access public housing, because of their status as 'single' and sometimes also because of their ethnic background (Cohen & Samzelius 2020).…”
Section: Welfare Divergence and Retrenchmentmentioning
confidence: 99%
See 1 more Smart Citation